DAYA TARIK HUMOR PADA IKLAN ANIMASI DALANG PELO - Intan Pradnyanita, A.A. Sagung; Santosa, Ngurah Adhi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Advertising is one of the ways to introduce a product or service to the people to buy or use it. Currently, advertising is very easy to find on various occasions in people's life. Advertisements have to be able to display the information about products or services offered in unique and creative ways, thus the advertisements often utilize creative ideas, visual strategies, attractive copywriting, visual effects, and the selection of roles in advertisements to attract consumers' attention. One of the creative strategies used in advertising is to use the attraction of humor and the selection of contemporary promotional media, such as social media. Dalang Pelo is one of the Instagram accounts which is active in producing creative content that creates animation that tells the story of the humor and ridiculousness of the main character named Acil. Through creative content in the form of animation with the presentation of funny stories, it creates the opportunities for companies that want to cooperate with Dalang Pelo accounts in advertising products, services or promotional activities.